SAT0459 Occurrence of lymphoma in systemic lupus erythematosus: a case-series of 38 patients. (12th June 2018) - Huscenot, T.; Mathian, A.; Martin, M.; Deligny, C.; Allain, J.-S.; Pha, M.; Costedoat-Chalumeau, N.; Le Guern, V.; Pugnet, G.; Cohen-Aubart, F.; Lavigne, C.; Haroche, J.; et al.
Abstract : Background: Patients with systemic lupus erythematosus (SLE) are at higher risk than the general population of developing lymphoma. Relatively little is known about the risk factors, the treatment and the outcome of lymphoma in SLE. Objectives: We aimed to describe a cohort of patients suffering from lymphoma in the setting of SLE and to study the risk factors of developing this complication. Methods: We collected clinical data of SLE patients with confirmed lymphoma in a multicentric and retrospective study. SLE patients were eligible for the study if they fulfilled at least 4 of the 1997 ACR criteria for SLE. Exclusion criteria were HIV or C hepatitis infection. Results: We included 38 patients (34 women and 4 men) coming from 10 different French University Hospitals. The lymphoma occurred after the diagnosis of SLE for 35 patients, with a median (range) time of 8.8 years (0–39). In their past or present medical history, 11 (29%) had a haematological involvement (5 immune thrombocytopenias, 4 autoimmune hemolytic anemias and 2 patients with both). Nine patients (24%) had associated Sjögren syndrome. 22 patients (58%) had a polyclonal hypergammaglobulinemia. Before the occurrence of the lymphoma, 18 patients (47%) had received an immunosuppressant during a median (range) period of 67 months. 6–195 17 patients had an indolent B cell lymphoma (IBCL), 14 a high-grade B cell lymphoma (11 diffuse large B cell lymphoma [DLBCL]; 2 a primary DLBCL of the central nervous system; and 1 an iatrogenic immunodeficiency-associated lymphoproliferative disorder), 5 a Hodgkin's disease (HD), and 2 a T cell lymphoma. The EBER in situ hybridization stain was positive in 7 of the 13 patients assessed (3/3 HD, 3/7 DLBCL and 1/2 IL) and was not associated with the immunosuppressant prescription. The median (range) of the survey after the lymphoma was 28.5 month (0–235.1). The 14 DLBCL patients except 1 were treated with chemotherapy: 4 died, 9 were in complete remission and 1 was in progression. Regarding the 17 IBCL, 9 patients were treated with chemotherapy, 2 patients with surgery, 1 patient with radiotherapy and 5 patients were not treated: 3 patients had to short follow-up or were lost, 1 died, 2 developed a DLBCL, 4 were stable and 7 were in complete remission. The 5 HL were treated with chemotherapy and all were in complete remission. Conclusions: IBCL and DLBCL were the most common type of lymphomas in SLE patients. Data suggest a role for EBV but not for exposition to immunosuppressant in the pathogenesis of SLE-associated lymphoma. The outcome of lymphoma in the setting of SLE seems not different from the outcome of lymphoma in the general population. A case-control study is ongoing to study the risk factors associated with the occurrence of lymphoma in SLE Disclosure of Interest: None declared